An Analysis of Speech Act Strategy Used by Teacher in Teaching English as Foreign Language - Sriwahyuni, Sriwahyuni; Noni, Nurdin; Jafar, Muhammad Basri (BATARA DIDI : English Language Journal, 2024)
This research elucidated and examined the practice of teacher speech actions in the context of teaching English as a second language. The present study used qualitative research approaches. The present study investigated the verbal expressions of professors at Universitas Negeri Makassar. The data consisted of teacher comments and other utterances. The researcher actively participated in all aspects of this inquiry, including the whole process from concept to data report. Data was obtained by audio video and observational methods. The data was gathered, documented, chosen to align with study objectives, organized into data sheets, and then analyzed and assessed using Searle's speech act theory. The study revealed that the teacher used many speech acts, including locutionary, illocutionary, and perlocutionary activities. There were 122 words (51.69%) that had locutionary actions. There was a total of 107 illocutionary activities, accounting for 45.33% of the utterances, and 7 perlocutionary acts, or 2.97%. Teachers using speech acts in English instruction use them to validate, rectify, elucidate, apprise, and assert on behalf of their students. Directives include a range of directives, such as reminders, requests, instructions, and warnings. Expressive words include expressions of gratitude, warm greetings, praises, and dissatisfaction. Compliments are reciprocal in nature. Instructions were used by teachers the most often, accounting for 93 instances or 45.15 percent of all speech activities. The purpose of the teacher's speech was to pose an inquiry.